www.congregationalresources.org: A Guide to Resources for Building Congregational Vitality - Bass, Richard (Rowman & Littlefield Publishers, 2004)
An ever-increasing number of resources compete for the attention of congregational leaders. With a seemingly endless number of choices, finding the best resource on a particular topic for a specific congregation is an often daunting challenge. www.congregationalresources.org, is an invaluable companion to the groundbreaking online version of Alban Institute’s and Indianapolis Center for Congregation’s jointly researched and produced Congregational Resource Guide, launched in 2001 and accessed by thousands of seekers each week. The book conveniently and cogently puts the rich array of important resources into context by examining in depth, the key books, organizations, Web sites, and people that will help leaders gain an understanding of important issues facing their congregations. The book features ten overviews of important topics by widely recognized experts in their fields, including Amy Sherman on Community Ministry, Tom Fischer on Congregational Health, Lee Ramsey on Preaching, Paul Chaffee on Leadership, John Janka on Evaluation, and Jean Trumbauer on Lay Ministry. Each essay is accompanied by an annotated list of selected resources for researching further information. Helpful guides for using these valuable resources to promote and encourage congregational understanding and transformation are also included.